Pragmatics : the basics - Clark, Billy (London ; New York : Routledge, 2021)
"Pragmatics : The Basics is an accessible and engaging introduction to the study of the meaning of language and nonverbal communication in context. Including nine chapters on the history of pragmatics, current theories, the application of pragmatics, and possible future developments in the field, this book: offers a comprehensive overview of key ideas in contemporary pragmatics and how these have developed from and beyond the pioneering work of the philosopher Paul Grice; draws on real-world examples such as political campaign posters and song lyrics, to demonstrate how we convey and understand direct and indirect meanings; explains the effects of verbal, nonverbal, and multimodal communication and how the same words or behavior can mean different things in different contexts, including what makes utterances more or less polite; highlights key terms and concepts throughout and provides chapter-end study questions, further reading suggestions, and a glossary. Written by an experienced researcher and teacher, this book will be an essential introduction to this topic for all beginning students of English Language and Linguistics"--
Introduction: the very basics -- Introduction: the very basics -- Adjusting the maxims: neo-Gricean pragmatics -- Principles and heuristics: relevance theory -- Managing interactions: (im)politeness -- What words can do: speech acts -- Beyond words: prosody -- Beyond words: nonverbal and multimodal communication -- The future: developing pragmatic theories.
Keywords: Pragmatics